2023
DOI: 10.1002/smll.202302613
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Mediated the Diagnosis and Therapy of Glioblastoma: Bypass or Cross the Blood–Brain Barrier

Abstract: Glioblastoma is one of the most aggressive central nervous system malignancies with high morbidity and mortality. Current clinical approaches, including surgical resection, radiotherapy, and chemotherapy, are limited by the difficulty of targeting brain lesions accurately, leading to disease recurrence and fatal outcomes. The lack of effective treatments has prompted researchers to continuously explore novel therapeutic strategies. In recent years, nanomedicine has made remarkable progress and expanded its app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 144 publications
0
13
0
Order By: Relevance
“…Physiologically, the BBB is a biofilm barrier that protects and maintains CNS function 31,40 . Pathological conditions usually involve pathological “disruption” of BBB function, with disruption of TJs structure, decreased expression of TJ proteins, and increased BBB permeability 12,41 . On the one hand, pathological “disruption” of BBB function leads to disruption of the balance of the CNS internal environment, leakage of toxic substances from the bloodstream into the CNS, formation of cellular infiltrates, abnormal molecular transport and clearance, accelerated disease progression, and poor disease prognosis.…”
Section: Blood–brain Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologically, the BBB is a biofilm barrier that protects and maintains CNS function 31,40 . Pathological conditions usually involve pathological “disruption” of BBB function, with disruption of TJs structure, decreased expression of TJ proteins, and increased BBB permeability 12,41 . On the one hand, pathological “disruption” of BBB function leads to disruption of the balance of the CNS internal environment, leakage of toxic substances from the bloodstream into the CNS, formation of cellular infiltrates, abnormal molecular transport and clearance, accelerated disease progression, and poor disease prognosis.…”
Section: Blood–brain Barriermentioning
confidence: 99%
“…Therefore, to avoid irreversible damage to normal brain tissue caused by whole‐brain irradiation, irradiation is performed primarily in the tumor area 11 . As a rule, chemotherapy is used to treat malignant tumors, but chemotherapeutic agents have limitations such as the blood–brain barrier (BBB) and toxic side effects of the drugs 12–14 . For low‐grade gliomas, cure criteria can be achieved after total surgical resection, with a median survival of up to 50 years.…”
Section: Introductionmentioning
confidence: 99%
“…Human serum albumin (HSA), the primary component of serum proteins, serves as a versatile carrier for therapeutic and diagnostic drugs with inflammation-targeting properties. Given its naturally biocompatibility, biodegradability, ease of production, and cost-effectiveness, HSA stands as a promising multifunctional drug carrier ( 22 24 ). In recent years, several preclinical studies have reported albumin-based biomimetic nano-systems as drug delivery vehicles for RA treatment in animal models ( 25 27 ).…”
Section: Drugs Delivery Systemmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM), characterized by its poor prognosis and a 5-year survival rate below 5%, presents a significant therapeutic challenge due to the blood-brain barrier (BBB) and blood-brain tumor barrier (BBTB) impeding effective drug delivery. Current systemic chemotherapies, including Temozolomide (TMZ), demonstrate limited efficacy largely due to these barriers and inherent drug resistance. , Enhancing drug lipophilicity to facilitate BBB crossing has been explored, , but this often results in poor penetration and systemic toxicity. To address these challenges, recent advances in nanomedicine have led to the development of nanodrug delivery systems (NDDS), offering strategies for therapeutic delivery to brain tumors. …”
Section: Introductionmentioning
confidence: 99%
“…To address these challenges, recent advances in nanomedicine have led to the development of nanodrug delivery systems (NDDS), offering strategies for therapeutic delivery to brain tumors. 9 15 …”
Section: Introductionmentioning
confidence: 99%